(untitled) (Research, Society and Development, 2024)
Introduction: Blood has essential components for life. Hemovigilance, based on hemotherapy, guarantees the safety of the donor and recipient. Objective: To investigate the transfusion act and the hemovigilance service in the Emergency Care Unit of Icoaraci, Belém, Pará. Methodology: This is an exploratory, qualitative and quantitative study, of the action research type, using convenience sampling , being retrospective for the period from September to December 2022 and prospective for the period from January to February 2023, with a situational diagnosis of the service carried out and the proposition of a model of action for the pharmaceutical professional in the process. Results: It is recorded that December 2022 presented the highest number of blood transfusions, with February 2023 presenting the highest number of post-transfusion reactions (10 cases). Of the transfused patients, there was a prevalence of female patients (55%), with an average age of 42 years. Among the clinical manifestations, the hypertensive peak stood out. The most used blood component was packed red blood cells. Non-conformities were also observed in relation to the technical regulations for hemotherapeutic procedures. Finally, Continuing Education was used to guide the correct performance of the transfusion act. Conclusion: It is recommended to reflect on the importance of the pharmacist’s role in hemotherapy; as well as their inclusion in the multidisciplinary team responsible for hemotherapy.